Model Lintnera - dywidenda a struktura akcjonariatu - Wójcikowska, Urszula; Wójcikowski, Rafał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The Lintner model, has been successfully tested on numerous world markets, both developed and emerging ones. The article is an attempt to verify the model on the Polish market and structure of the shareholders. The estimations confirm the model holds and earnings and structure of shareholders best explain the dividend changes. Positive empirical model verification is significant not only for investors applaying it to anticipate future dividends, but also for equity valuation in DCF models based on future dividends. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 525-530